Potential and Obstacles in Cultural Heritage Development in Tanjungpinang City - Nika Purnamasari; Zikri Raudhatul Ahsan; Ari Ridho Susanto; Bayu Saputra; Sri Wahyuni (PT FORMOSA CENDEKIA GLOBAL, 2023)
The city of Rebah is a place for tourists to visit. In the city of Rebah, there are several relics such as tombs, collapsed buildings, docks. The city of Rebah has an area of ​​4 hectares, has good views, the view from the pier directly shows the Carang river bridge and there are mangrove trees. In this research the author used qualitative methods. According to Bogdan and Taylor (1975:5) defines that